HISTORY OF SURKHONDARYA AND ZARAUTSOY EMERGENCE OF FINE ART - Davronova Farzona Azamatovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: In this article, information about the history of Surkhandarya, stone sources related to the Stone Age, the first stage of human development, i.e. texts, inscriptions, images, and paintings, as well as the first examples of stone tools , and the unique resources of Zarautsoi, which were turned into an art history reserve for the first time, are highlighted.